1975
DOI: 10.1007/bf00237350
|View full text |Cite
|
Sign up to set email alerts
|

Response of medial preoptic neurons to electrical stimulation of the mediobasal hypothalamus, amygdala and mesencephalon in normal, serotonin or catecholamine deprived female rats

Abstract: Single cell activity from preoptic neurons was extracellularly recorded in normal female rats and the effects of electrical stimulation of the mediocortical amygdala (AMY), the N. med. raphes (MES) and the mediobasal hypothalamus (MBH) was tested. 1. One type of preoptic neurons (55%) reacted with primary excitation to a single electrical stimulus of AMY, MES or MBH, which was usually followed by a period of postexcitatory inhibition. Another type of neurons (29%) were first inhibited after stimulation of AMY,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Similar findings have been reported in earlier studies of rostral hypothalamic neurones (Fenske et al 1975;Gardner & Phillips, 1977 b), but the significance of these observations is unclear. It is generally accepted that the inhibition of activity generated by ionophoretic application of an excitant amino acid is due to a post-synaptic mechanism (Krnjevic, Randic6 & Straughan, 1966).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar findings have been reported in earlier studies of rostral hypothalamic neurones (Fenske et al 1975;Gardner & Phillips, 1977 b), but the significance of these observations is unclear. It is generally accepted that the inhibition of activity generated by ionophoretic application of an excitant amino acid is due to a post-synaptic mechanism (Krnjevic, Randic6 & Straughan, 1966).…”
Section: Discussionsupporting
confidence: 89%
“…Reduction of the frequency of occurrence of synaptic inhibition in the preoptic-anterior hypothalamus by tetanus toxin provides valuable confirmatory evidence in support of the earlier suggestion that such inhibition is mediated by amino acid transmitters. Conversely the lack of effect of pretreatment with the anti-serotonin neurotoxins 5,7-dihydroxytryptamine and parachlorophenylalanine provides no evidence for any role of 5-HT in mediating such synaptic inhibition, confirming the earlier report of Fenske et al (1975) that 5,6-dihydroxytryptamine had no effect on synaptic inhibition in the rostral hypothalamus. Since anatomical studies have shown the major source of tryptaminergic afferents to the rostral hypothalamus to arise in the medial raphe nucleus (Azmitia & Segal, 1978) it is perhaps not surprising that stimulation sites in the periaqueductal grey matter appear to activate non-tryptaminergic inhibitory mechanisms.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Lesion and stimulation studies have shown that the caudal brainstem reticular formation (CBS) and the preopticoanterior hypothalamic area (POAH) of the basal forebrain promote sleep and synchronization of the EEG (Nauta, 1946; Sterman, and Clemente, 1962; Moruzzi, 1972; Mallick et al, 1984, 1986) and also that these areas are rich in sleep‐active neurons (Eguchi and Satoh, 1980; Mallick et al, 1983; Kaitin, 1984; McGinty and Szymusiak, 1988). The effects of one of the sleep‐waking‐regulating areas on neurons located in other such areas have been studied (Mancia et al, 1974; Fenske et al, 1975; Mallick et al, 1984, 1986; Szymusiak and McGinty, 1989; Macchi and Mancia, 1990; Osaka and Matsumura, 1994). However, becasuse those investigations were not conducted on freely moving animals, the effects on REM sleep‐related neurons could not be studied, nor could the neuronal activities be correlated with other associated behaviors of the animals.…”
mentioning
confidence: 99%
“…Similarly projections from the preoptic area afferent to the periaqueductal grey matter have recently been demonstrated, using anterograde (Aghajanian & Wang, 1977) and orthograde (Conrad & Pfaff, 1976;Swanson, 1976;Swanson, Kucharczyk & Mogenson, 1978) tracer techniques. Electrophysiological evidence concerning the anatomically demonstrated reciprocal mid brain-preoptic connexions is incomplete although it has been shown that stimulation of the median raphe nucleus (Fenske, Ellendorff & Wuttke, 1975) 54 MIDBRAIN CONTROL OF PREOPTIC EXCITABILITY and mesencephalic reticular formation (Gardner & Phillips, 1977) may alter the excitability of unidentified preoptic neurones. The present investigation provides details of mid brain-preoptic connexions, and demonstrates the predominately inhibitory influence of periaqueductal grey matter stimulation on the spontaneous, synaptic and ionophoretically evoked activity of neurones in the medial preoptic area, including those identified as projecting to the mediobasal hypothalamus (Dyer, 1973).…”
mentioning
confidence: 99%